Anthropometric Profile of Mentally Challenged Children (Indian Journal of Public Health Research & Development, 2020)
A concise report on mentally challenged children was focused on to their health and wellbeing by assessingtheir somatotype characteristics. For this study 25 (male) participants, age ranging in between 14 - 18 years,trainable and educable mentally challenged without any multiple disabilities were selected from SpecialSchool for Mentally Challenged People under Department of Teacher Training & Non-formal Education,Jamia Millia Islamia, New Delhi. Purposive sampling method and Ex-post facto design were applied. Byusing Heath- Carter Anthropometric Method each subject was somatotyped. Analysis of Data done throughSOMATOTYPE (Computer Programs for Somatotype Analysis) to calculate somatotypes, descriptiveand comparative statistics and plotting somatocharts with mean, standard deviation. The result clearlyindicated that mentally challenged participants have low level of body fat and observed more percentagein mesomorphic and ectomorphic category and it has been observed that they all were having improperskeleto-muscular development, unbalanced lifestyle. So, it is necessary for mentally challenged participantsto involve in special physical education program to develop their fitness level.
Keywords: Somatotype, Heath- Carter, somatometry, somatochart, somatoplot.